2020
DOI: 10.1101/2020.04.21.052852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The lemur baseline: How lemurs compare to monkeys and apes in the Primate Cognition Test Battery

Abstract: 28Primates have relatively larger brains than other mammals even though brain tissue is 29 energetically costly. Comparative studies of variation in cognitive skills allow testing of 30 evolutionary hypotheses addressing socioecological factors driving the evolution of primate 31 brain size. However, data on cognitive abilities for meaningful interspecific comparisons are 32 only available for haplorhine primates (great apes, Old-and New World monkeys) although 33 strepsirrhine primates (lemurs and lorises) se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 93 publications
1
16
0
Order By: Relevance
“…The opposite pattern was found for ruffed lemurs in that shyer subjects who took longer to approach and spent less time in the testing area performed better in the social PCTB tasks than their bolder conspecifics. This was not the case for ring-tailed lemurs whose temperament did not correlate with performance in the physical or social tasks of the PCTB ( Fichtel et al, 2020 ). Olive baboons, particularly males, spent more time next to new objects than long-tailed macaques and showed a shorter approach latency toward new stimuli than long-tailed macaques, particularly females.…”
Section: Overview Of Studies On Non-cognitive Factors That Potentiallmentioning
confidence: 88%
See 4 more Smart Citations
“…The opposite pattern was found for ruffed lemurs in that shyer subjects who took longer to approach and spent less time in the testing area performed better in the social PCTB tasks than their bolder conspecifics. This was not the case for ring-tailed lemurs whose temperament did not correlate with performance in the physical or social tasks of the PCTB ( Fichtel et al, 2020 ). Olive baboons, particularly males, spent more time next to new objects than long-tailed macaques and showed a shorter approach latency toward new stimuli than long-tailed macaques, particularly females.…”
Section: Overview Of Studies On Non-cognitive Factors That Potentiallmentioning
confidence: 88%
“…Similarly, older chimpanzees and bonobos performed better in some of the physical tasks (causality scale) but not as well as younger individuals in some social tasks (Theory of Mind scale, Herrmann et al, 2010 ). In the other studies applying the PCTB, no such age-effects on cognitive performance were reported ( Schmitt and Fischer, 2011 ; Fichtel et al, 2020 ). Another interesting finding was that high levels of curiosity appeared to alleviate cognitive decline in marmosets ( Gokcekus, 2020 ).…”
Section: Overview Of Studies On Non-cognitive Factors That Potentiallmentioning
confidence: 89%
See 3 more Smart Citations